The pleiotropic contribution of genes in dopaminergic and serotonergic pathways to addiction and related behavioral traits - Antón-Galindo, Ester; Cabana-Domínguez, Judit; Torrico, Bàrbara; Corominas, Roser; Cormand, Bru; Fernàndez-Castillo, Noèlia (Frontiers in Psychiatry, 2023)
Co-occurrence of substance use disorders (SUD) and other behavioural conditions, such as stressrelated, aggressive or risk-taking behaviours, in the same individual has been frequently described. As dopamine (DA) and serotonin (5-HT) have been previously identified as key neurotransmitters for some of these phenotypes, we explored the genetic contribution of these pathways to SUD and these comorbid phenotypes in order to better understand the genetic relationship between them. We tested the association of 275 dopaminergic genes and 176 serotonergic genes with these phenotypes by performing gene-based, gene-set and transcriptome-wide association studies in 11 genome-wide This is a provisional file, not the final typeset article association studies (GWAS) datasets on SUD and related behaviours. At the gene-wide level, 68 DA and 27 5-HT genes were found to be associated with at least one GWAS on SUD or related behaviour. Among them, six genes had a pleiotropic effect, being associated with at least three phenotypes: ADH1C, ARNTL, CHRNA3, HPRT1, HTR1B and DRD2. Additionally, we found nominal associations between the DA gene sets and SUD, opioid use disorder, antisocial behaviour, irritability and neuroticism, and between the 5-HT-core gene set and neuroticism. Predicted gene expression correlates in brain were also found for 19 genes DA or 5-HT genes. Our study shows a pleiotropic contribution of dopaminergic and serotonergic genes to addiction and related behaviours such as anxiety, irritability, neuroticism and risk-taking behaviour, highlighting a role for DA genes, which could explain, in part, the co-occurrence of these phenotypes.